Impact of social relationships on electronic word of mouth in social networking sites: a study of Indian social network users. (2017) - Sharma, Smita; Rehman, Asad
This study focused on the understanding of consumers' use of social networking sites as a vehicle for electronic word of mouth. The hypotheses examined the impact of social relationship variables-social capital, tie strength, attitude homophily, background homophily, trust, normative influence, and informational influence on electronic word of mouth behaviour in social networking sites. For testing the hypothesised relationships between the predictors and electronic word of mouth behaviour variables, structural equation modelling (SEM) was applied on the data collected from social networks' users. Exploratory factor analysis (EFA) was conducted, followed by confirmatory factor analysis (CFA). It was concluded that social capital, background homophily, normative influence, informational influence emerged to be strong significant predictors of electronic word of mouth, and attitude homophily and trust were found to be partially significant. Only tie strength was not found to be a significant predictor.